(Il)Legitimacy a study on the media's influence on the public's perceived legitimacy of the MILF and the NPA - Quililan, Isabella Danielle G. 1996-; San Juan, Dannica Marie D.P (2018)
"Legitimacy is an important factor in gauging and mobilizing support for Armed Non-State Groups (ANSGs). Their legitimacy, however, largely depends on the perception of the public. With the Cultivation Theory as its theoretical foundation, this study examined how people's exposure to TV news programs and online news articles on the Moro Islamic Liberattion Front (MILF) and the New People's Army (NPA) influence their perceived legitimacy of these groups. A survey was conducted with 409 respondents from Metro Manila to find out the public's level of exposure to media news reports on the MILF and NPA, as well as their perceived legitimacy of these two ANSGs. Additionally, content analysis of pertinent reports from select local TV news programs and online news sites was undertaken. It was found that the MILF had a generally positive portrayal in the TV news programs analyzed, while the NPA has a generally negative portrayal. From its findings, the study concludes that news media have cultivation effects on the public's perceived legitimacy of the MILF and the NPA. However, the presence of cultivation effects is stronger for the people's perceived legitimacy of the NPA than the MILF. Moreover, cultivation effects are stronger for TV news programs than online news sites."